Synthesis, Molecular Modeling, and Biological Activity of Zinc(II) Salts with 1,4-Bis(benzimidazol-2-yl)benzene - G. Krishnamurthy (Journal of Chemistry)
Zinc(II) halides and perchlorate react with 1,4-bis(benzimidazol-2-yl)benzene (L) in 1 : 2 molar ratio in n-butanol/2-methoxy ethanol (10 mL) at refluxing temperature to produce white/pale yellow-colored complexes of the formulae [ZnCl2L]H2O, [ZnBr2L]3H2O, and [Zn(OClO3)2L]HOCH2CH2CH2CH3. Zinc(II) iodide also reacts with L in 1 : 2 molar ratio in n-butanol (HOCH2CH2CH2CH3) to yield white-colored complex of the formula [ZnL2(OCH2CH2CH2CH3)2]. The complexes were characterized by elemental analysis, molar conductance measurements, thermal analysis, and IR, 1H-, 13C-NMR spectral studies. The complexes showed significant anthelmintic activity. The minimum energy configuration has been obtained for the zinc complexes using molecular modeling Pro Plus; a tool developed by ChemSW, inc, USA.